Framing the Household Sustainable Consumption and Lifestyle in Malaysia: The Policy Implications - Safitri Zen, Irina; Ebrahimi, Mansoureh; Wahyu Titisari, Prima; Hendrayani, Yani (International Journal of Psychosocial Rehabilitation, 2020)
Given the plethora of choices and the abundance of products available in the market, household roles in practicing sustainable consumption and lifestyle in their daily life are crucial. As a newly industrialized country, Malaysian consumers are experiencing high consumerism spirits due to strong purchasing power. Hence, reorienting the complexities of consumption patterns towards sustainability requires defragmentation, prioritization, and gradually changing to find more practical and strategic actions to overcome the barriers and policy intervention. Thus, this study aims to explore and analyze to what extend the sustainable consumption and lifestyle are being practices, ii. What are the barriers to foster the gradual changes to performs such behavior and iii.how the complexities of consumption structure to create the conducive environmental for behavioral changes towards sustainable behaviour. The study found the contextual factors of availability of green products and barriers that need to be overcome to develop the household sustainable lifestyle. Most of the household sustainable lifestyle practices and purchases are driven by economic rationalities rather than environmental reasons. The complexities of the interrelatedness of consumption are structured into an integrative framework of household sustainable lifestyle and consumption, which recognizes the contextual factors of sustainable purchases and barriers to strengthening sustainable behavior. From this study, four points of policy intervention levels are recognized to overcome the barriers in performing sustainable lifestyles and consumption. The four are product innovation, technical innovation, governance approaches, and knowledge, awareness, and advocacy. Various policy instruments related to sustainable lifestyle and consumption are proposed by considering the contextual factor of sustainable consumption and lifestyle in Malaysia.